Review of the endemic Neotropical genus Agenamyia Albuquerque (Diptera: Muscidae) with the description of new species from South America - Carvalho, Claudio José Barros De; Wolff, Marta; Haseyama, Kirstern Lica Follmann; Fogaça, João Manuel (Zootaxa, 2023)
Agenamyia Albuquerque, an endemic neotropical genus with two species, has been revised to include three new species: Agenamyia colombiana de Carvalho, Wolff & Fogaça sp. nov. from Envigado; Agenamyia maculata de Carvalho, Wolff & Fogaça sp. nov. from El Retiro; and Agenamyia timida de Carvalho, Wolff & Fogaça sp. nov. from Sopetrán, all localities in Antioquia, Colombia. This review presents an identification key for all species, including color images and illustrations of male and female terminalia. The distribution of all species is mapped and discussed.